Comprehensive evaluation of non-coding RNA-mediated autophagy regulation in myocardial ischemia-reperfusion injury - Song, Zhongyang; Suo, Chang; Liu, Yongqi; Jin, Ling; Xie, Xiaodong; Liu, Jian; Yu, Bo; Wang, Yanzhen; Zhang, Zhiming; Xie, Dingxiong (Frontiers in Pharmacology, 2025)
Ischemic heart disease remains a major global health challenge, with myocardial ischemia-reperfusion injury (MIRI) being one of its most common and severe pathophysiological complications. The pathogenesis of MIRI is multifaceted, involving oxidative stress, inflammatory responses, apoptotic pathways, and autophagic regulation. Notably, autophagy exerts a dual regulatory effect, where maintaining optimal autophagic flux is essential for cardiac homeostasis. Emerging evidence underscores the crucial role of non-coding RNAs (ncRNAs) in modulating these pathological processes. In particular, long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs) have been identified as key regulators of autophagy-mediated MIRI progression through complex molecular networks. This review provides a systematic analysis of the molecular pathways through which ncRNAs influence MIRI pathogenesis, with a specific focus on their autophagy-regulatory mechanisms. These insights may enhance our understanding of MIRI pathobiology and facilitate the development of novel therapeutic strategies.